Organ donation after euthanasia, morally acceptable under strict procedural safeguards - Dijk, Gert; Bruchem‐Visser, Rozemarijn; Beaufort, Inez (Clinical transplantation, 2018)
In this paper, we will present a case of organ donation after active euthanasia (ODE) in the Netherlands from a patient who had his life ended at his explicit and voluntary request. The form of ODE we describe here concerns patients who are not unconscious and on life support, but who are conscious and want to have their life ended because of their hopeless and unbearable suffering, for instance due to a terminal illness such as Amyotrophic Lateral Sclerosis (ALS) or Multiple Sclerosis (MS). This form of ODE is of course only possible in jurisdictions where euthanasia is allowed. In these jurisdictions, organ donation after euthanasia is an option that may be considered. We believe ODE is worthwhile to pursue, as it can strengthen patient autonomy, can give meaning to the inevitable death of the patient, and be an extra source of much needed donor organs. To ensure voluntariness of both euthanasia and organ donation and avoid conflict of interest by physicians, ODE does need strict procedural safeguards however. The most important safeguard is a strict separation between the 2 procedures. The paper discusses several ethical issues such as who should broach the subject of organ donation and who should perform the euthanasia, and how a conflict of interest can be avoided.